Pengaruh pemberian konsentrat pada waktu yang berbeda terhadap keberhasilan inseminasi buatan pada sapi Persilangan Limousin - Yadi Malda; Nurul Layla; Auliya Puspita Anugrah Yekti; Asri Nurul Huda; Kusmartono Kusmartono; Trinil Susilawati (Livestock and Animal Research, 2022)
Objective: This study aims to evaluate the effect of providing concentrate at different times on the success of artificial insemination in limousin crossbred cow. The material in the study used limousin crossbred cows as many 45 cows, 15 each treatment, cattle between 1,5-6 years old, (BCS) 4-6 (standard 1-9).Methods: This research method uses experimental field trials. Data analyzed used Completely Randomized Block Design (RCBD), grouping based on body weight (BW). Analyzed by ANOVA continued by Duncan Multiple Range Test (DMRT). Treatment T0: field grass + Bio ATP, T1: field grass + concentrate 14 days before oestrus and 7 days after estrus + Bio ATP T2: field grass + concentrate 7 days before oestrus and 7 days after estrus + Bio ATP.Results: The result show that DM consumption T0 (7,74 kg), T1 (12,54 kg) and T2 (12,56 kg), CP consumption T0 (0,62 kg), T1 (0,72 kg) and T2 (0,69 kg), TDN consumption T0 (4,32 kg), T1 (5,23 kg) and T2 (5,17 kg). NRR1 in T0 treatment, T1 and T2 continued 86,67%, 60%, and 73,33%, NRR2 in T0 treatment, T1 and T2 continued 86,67%, 60% and 66,67%. CR in T0 treatment (66,67%), T1 (33,33%) and T2 (26,67%). CR in T0 treatment, T1 and T2 continued 80%, 66,67% dan 40%.Conclusions: The conclusion of this research is that using concentrate has a lower percentage of pregnancy 66,67% and 40% without using concentrate at 80%.